2018
DOI: 10.1177/1758835918794628
|View full text |Cite
|
Sign up to set email alerts
|

Towards precision medicine: linking genetic and cellular heterogeneity in gastric cancer

Abstract: Molecular and cellular heterogeneity are phenomena that are revolutionizing oncology research and becoming critical to the idea of personalized medicine. Recent comprehensive molecular profiling has identified molecular subtypes of gastric cancer (GC) and linked them to clinical information. Moreover, GC stem cells (gCSCs) have been identified and found to be responsible for GC initiation and progression, Helicobacter pylori oncogenic action and therapy resistance. Addressing molecular heterogeneity is critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 106 publications
0
32
0
Order By: Relevance
“…Treatment consists of surgery with additional chemo/radiotherapies, but the number of relapse cases remains high with a five-year survival rate less than 20%; less than 5% for advanced unresectable or metastatic cases which account for about 80% patients at diagnosis [ 2 ]. There exists at present no targeted therapy except for Herceptin which can be used to treat HER2+ GC cases comprising only 30% of GCs [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment consists of surgery with additional chemo/radiotherapies, but the number of relapse cases remains high with a five-year survival rate less than 20%; less than 5% for advanced unresectable or metastatic cases which account for about 80% patients at diagnosis [ 2 ]. There exists at present no targeted therapy except for Herceptin which can be used to treat HER2+ GC cases comprising only 30% of GCs [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histological classification per se is not enough to explain the high complexity of GC [6]. Recent technical advances along with the efforts of international research consortiums, such as the Cancer Genome Atlas (TCGA) Research Network and Asian Cancer Research Group (ACRG), have led to remarkable progress in elucidation of the genomic landscape of GC [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…CSCs has been studied as a prospectively curative approach against a variety of malignancies. [4][5][6] We found that Cygb knockdown aggravates the formation of HCC sphere, whereas Cygb restoration inhibits the formation of HCC sphere in vitro (Figure 2E-H). CD133…”
Section: Cscs Are a Crucial Subpopulation Of Cancer Cells Targetingmentioning
confidence: 90%
“…Cancer stem cells (CSCs) are the crucial subpopulation of cancer cells that determine tumor initiation, self‐renewal, and heterogeneity. Targeting CSCs may provide a curative approach to overcome therapy resistance and prevent tumor progression . Accumulating evidences indicated that the interaction of ONS with CSCs promotes tumorigenesis, progression and cancers resistance to chemoradiotherapies.…”
Section: Introductionmentioning
confidence: 99%